Agroturismo y Desarrollo Turístico de la parroquia Cebadas, cantón Guamote, provincia Chimborazo. - Gualán Poma, Inés Yolanda (2023)
Ecuador has a geographic, sociocultural, and natural potential that favors promoting agrotourism development as an alternative to sustainable development. Therefore, the purpose of this study is to determine the relationship between agrotourism and tourism development in the Cebadas Community, located in the Guamote Canton of the Chimborazo Province. The research used a mixed methodological approach, which allows an accurate measurement of relationships between variables without the interference of unrelated factors. The survey and interview were used as study techniques, which experts validated, and Alpha-Cronbach was used to see the tool's reliability. The following were considered as categorical dimensions: ancestral cultural practices, traditional agricultural manifestations, experiential tourism experience, and sustainability principles. The SPSS program was used to test the hypothesis by using the chi-square test. The obtained results showed that agrotourism has no relationship with tourism development; likewise, ancestral cultural practices and traditional agricultural practices have no relationship with tourism development despite the valuable cultural heritage that the parish has. However, the third hypothesis, the experiential tourism experience, has a direct relationship with tourism development. Therefore, it is essential to implement additional measures to promote the tourism offer. Considering the results within the framework of this research, it was proposed to create an agro-tourism package to put ancestral knowledge into practice through tourism, providing educational and authentic experiences to visitors.